Impact of Working Together for adults with autism spectrum disorder: a multifamily group intervention - Leann Smith DaWalt; Emily Hickey; Rebekah Hudock; Amy Esler; Marsha Mailick (Journal of Neurodevelopmental Disorders, 2021)
Abstract Background Adults with autism spectrum disorder (ASD) have lower engagement in their communities, higher rates of unemployment/underemployment, and continued difficulties with challenging behavior compared to their neurotypical peers. Multi-family psychoeducation emphasizes education and problem-solving with the goal of improving these outcomes for the individual with the disability. Methods Using a randomized waitlist control design, the present study evaluated a multi-family group psychoeducation intervention, Working Together , for adults on the autism spectrum without intellectual disability (n = 40). Five waves of data were collected at 3-month intervals. In this design, families in the intervention condition participated in intervention during the 6 months between baseline and time 3 data collection; the waitlist control condition received the intervention immediately after the time 3 data collection. We compared these two conditions, intervention group (n = 20) vs waitlist control group (n = 20), on key outcomes for the adults with ASD: engagement in work-related activities, engagement in meaningful activities, and behavior problems. Results Results indicated medium to large effect sizes associated with the Working Together intervention across key outcomes, including adults on the spectrum experiencing significant increases in meaningful activities and decreases in internalizing problems. Although increases in work-related activities were not statistically significant, an observed one-half of a standard deviation difference from before to after the intervention indicated clinically significant change. We also found maintenance of the treatment effect through 6 months post-treatment for the intervention group and replication of the treatment effect within the control group after they received the intervention. Conclusion Working Together is a promising multi-family group psychoeducation intervention designed to improve functioning during adulthood. These findings highlight the need for more intervention services research during adulthood and specifically the need for family-centered supports.